Evaluation the Effect of Swimming Time on Dental Erosion among Swimmers - Masomeh Mehdipour; Ali Taghavi Zenooz; Narges Gholizadeh; Aila Bahramian; Nastaran Sartip Pour (Islamic Dental Association of Iran, 2013)
Background and Aim: Erosion is a multi-factorial process that occurs during life and it happens by many external or internal factors . The current study aimed to evaluate the relation of swimming time and dental erosion among swimmers .   Materials and Methods : In this descriptive-analytical study, 84women individuals were selected. The case group included 42 swimmers who swam more than 6 hours per week and the control group comprised of 42 swimmers who swam less than 6 hours. The information regarding dental erosions and other data was collected by questionnaires. The dental erosion evaluation was performed using Smith-Knight index. X2 was utilized for statistical comparisons. The P-value of less than 0.05 was considered statistically significant .   Results: Findings revealed that the dental erosion proportions was similar among two groups and there was no relation between swimming time and dental erosion among swimmers (p-value= 0/6 , X2 = 0.26) .   Conclusion: There was no relation between swimming time and dental erosion among swimmers . Therefore, the role of swimming time on dental erosion was not proved .